Arranging play activities with missing items to increase object-substitution symbolic play in children with autism spectrum disorder. Issue 22 (23rd October 2021) - Lee, Gabrielle T.; Qu, Kezheng; Hu, Xiaoyi; Jin, Ning; Huang, Jingjing
Abstract: Purpose: Many children with autism spectrum disorder do not have symbolic play skills. The purpose of this study was to evaluate the effects of a training procedure on the acquisition, maintenance, and generalization of object-substitution symbolic play in children with autism spectrum disorder. Methods: A single-case experimental design (multiple-probe across four behaviors) was used. One girl (5 years) and two boys (4–5 years) participated in this study. The training procedure involved withdrawing necessary items in play activities, supplying multiple substitutes, and providing hierarchical assistive prompts. Each child's symbolic play responses across baseline, intervention, and follow-up conditions were recorded and graphed. Data analysis involved visual inspection of graphs. Results: The results indicated that the procedure effectively increased and maintained object-substitution symbolic play. Generalization to untaught play activities occurred in all children, and symbolic play increased in the free play setting for one child. Conclusions: Arranging play activities with missing items increased opportunities for children to engage in symbolic play. The training procedure can be used in clinical and educational settings as an initial step to establish and improve complex play behavior in children with autism spectrum disorder who lack such skills. IMPLICATIONS FOR REHABILITATION: Many children with autism spectrum disorder have inappropriate play behaviors and do not demonstrate symbolic play. Arranging play activities with missing items and systematic assistive prompts effectively increased object-substitution symbolic play. Generalization of symbolic play to untrained play activities occurred after the intervention.